DEVELOPING “EXIT” GAME TO OVERCOME SENIOR HIGH SCHOOL STUDENTS’ SPEAKING ANXIETY - Titania, Fani Nabila (RETAIN, 2022)
Speaking anxiety was one serious problem for senior high school students. It should handle as soon as possible because it could affect students' learning process. This study aimed to describe the development process, the validation, and the practicality of the "EXIT" game as a medium to overcome senior high school students' speaking anxiety. This study followed the ADDIE approach by Branch (2009) to develop the media. This study involved fifteen senior high school students and one teacher in playing this game. Besides that, the validation score for the media was 96 that could be considered "Valid and Applicable." According to the interview result, students felt enjoy and relax while speaking in front of their friends. They did not show their speaking anxiety. They also gave positive feedback toward the "EXIT" game. Furthermore, the teacher also gave an appraisal for the game. Based on the trial result, the primary goals had met. In short, the "EXIT" game was applicable for overcoming students' speaking anxiety. Keywords: Speaking Anxiety, EXIT game, Educational Game, ADDIE